TELAAH KESESUAIAN PERTIMBANGAN HAKIM DALAM PUTUSAN NOMOR 24/PID.SUS-ANAK/2022/PN MND TERHADAP UU SPPA - Muhammad Aqil Yuda Pratama; Ismawati Septiningsih (Verstek, 2023)
This writing analyzes the appropriateness of the judge's considerations in imposing a five-year prison sentence on a child with article 79 of the Law of the Republic of Indonesia Number 11 of 2012. In Decision Number 24/Pid.Sus-Anak/2022/PN Mnd it is known that a crime of violence has occurred with joint power carried out by children. The perpetrator was subject to Article 170 of the Criminal Code paragraph (2) 3rd of the Criminal Code and considered Law Number 11 of 2012 concerning the Juvenile Justice System because the perpetrator was a child. The purpose of this writing is to find out whether the judge's considerations in Decision Number 24/Pid.Sus-Anak/2022/PN Mnd are in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. As a result, the judge in hisconsiderations before passing the decision had considered Article 79 of the Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Justice System.Keywords: Consideration; Collective violence; Child